2021
DOI: 10.1186/s12951-021-00991-5
|View full text |Cite
|
Sign up to set email alerts
|

Injectable exosome-functionalized extracellular matrix hydrogel for metabolism balance and pyroptosis regulation in intervertebral disc degeneration

Abstract: Exosome therapy is a promising therapeutic approach for intervertebral disc degeneration (IVDD) and achieves its therapeutic effects by regulating metabolic disorders, the microenvironment and cell homeostasis with the sustained release of microRNAs, proteins, and transcription factors. However, the rapid clearance and disruption of exosomes are the two major challenges for the application of exosome therapy in IVDD. Herein, a thermosensitive acellular extracellular matrix (ECM) hydrogel coupled with adipose-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
118
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 47 publications
0
118
0
1
Order By: Relevance
“…Acidic pH adversely affects the proliferation of NPCs, and destroys the metabolic balance of the ECM, which limits the therapeutic potential of MSCs and is a negative factor affecting intervertebral disc repair (Huang et al, 2013). Moreover, ADMSC-Exos have also been found to suppress the MMP-13 expression, inhibit ECM decomposition in degenerative NPCs, and increase collagen II expression to promote ECM formation (Xing et al, 2021).…”
Section: Inhibiting Ecm Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Acidic pH adversely affects the proliferation of NPCs, and destroys the metabolic balance of the ECM, which limits the therapeutic potential of MSCs and is a negative factor affecting intervertebral disc repair (Huang et al, 2013). Moreover, ADMSC-Exos have also been found to suppress the MMP-13 expression, inhibit ECM decomposition in degenerative NPCs, and increase collagen II expression to promote ECM formation (Xing et al, 2021).…”
Section: Inhibiting Ecm Degradationmentioning
confidence: 99%
“…Studies have demonstrated that the secretion of inflammatory factors such as IL-1α, IL-1β, IL-6, IL-17, nuclear factor-κB p65 (NF-κB p65), TNF-α was increased in the NPCs from degenerative discs, and found that ADMSC-Exos could decrease the inflammation level (Zhang et al, 2021c). Additionally, ADMSC-Exos could inactivate the NLRP3 inflammasome, inhibit the expression of N-terminal gasdermin D (NT-GSDMD) and IL-1β proteins in degenerative NPCs, thereby more significantly reducing the inflammatory response (Xing et al, 2021). Besides, it was also shown that MSC-Exos significantly decrease NLRP3 expression and reduce caspase activation, hence downregulating the expression levels of downstream cytokines IL-18 and IL-1β, inhibiting NLRP3-mediated inflammatory pyroptosis in the degenerative NPCs (Zhang et al, 2020a).…”
Section: Inhibiting Inflammation Responsementioning
confidence: 99%
“…As a worldwide issue, the treatment of IDD based on stem cells has been widely studied; the rationales of stem cell therapy are considered as replenishing disc cells through multipotent differentiation, promoting proliferation of NP cells, enhancing immune privilege, and reducing apoptosis and anti-inflammation (Ma et al, 2015). Studies have already confirmed the potential therapeutic efficacy of MSC transplantation in the treatment of IDD, and by inheriting the characteristics of MSCs, exosomes could also treat IDD through protecting NP cells from apoptosis, mitigating the inflammatory responses of disc, and promoting the synthesis of ECM (Lu et al, 2017;Xing et al, 2021). The usage of exosomes as a cell-free product has continuously been regarded as substitute therapy against stem cell transplantation; the applications of exosomes rather than stem cells have advantages including low risk of tumorigenesis, malformations, and microinfarctions; convenience in collection and storage; increase of sustained biological activity; stability; and minimal immunogenicity when transplantation (Tao et al, 2018).…”
Section: Stem Cell-derived Exosomesmentioning
confidence: 99%
“…In the clinic, the applications of MSCs have been predominant due to their stronger functions than other cells, such as proliferation and differentiation ability in vitro ( Yeo et al, 2013 ), and MSCs also generate a large amount of exosomes, which have low immunogenic properties. Several studies have shown that MSC exosomes may be more appropriate than MSCs in stem cell-based therapies ( Yuan et al, 2020 ; Krut et al, 2021 ; Xing et al, 2021 ). Currently, numerous studies have reported the significance of exosomes in the treatment of IDD; the biological composition and functions of exosomes are based on different types of cells ( Wang et al, 2021 ).…”
Section: Exosomesmentioning
confidence: 99%
“…Interestingly, evidence from prior studies indicated that stem cells can serve their tissue repair function through paracrine exosomes. Exosomes, microvesicles with a diameter between 30 and 150 nm, can deliver growth factors, and proteins to target cells and exert their function [ 16 , 17 ]. Exosomes have many advantages compared to MSCs, including greater stability and low immunogenicity [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%